Gold Functionalized Platinum M12L24-Nanospheres and Their Application in Cyclization Reactions - Leenders, Stefan H.A.M; Dürr, Maximilian; Ivanovic-Burmazovic, Ivana; Reek, Joost N.H. (dvanced Synthesis & Catalysis, 2016)
Nanospheres can be formed by combining 24 bispyridinyl building blocks with a palladium or platinum precursor. These spheres can be functionalized on the inside with a gold(I) chloride complex leading to a high local concentration of gold(I) complexes. The high local concentration makes the neutral gold species an active catalyst. Furthermore, the platinum-gold spheres can be post-modified with a silver(I) salt to form cationic gold(I) catalysts. The platinum assemblies are demonstrated to be stable in the presence of various substrates and as a result several cyclization reactions have been carried out using these new spheres as catalysts. Higher conversions in a [4+2] cycloaddition are observed for the sphere catalyst compared to the mono-nuclear analogues. Also the cyclization of 1,6-enynes can be facilitated by the confined gold catalyst and high activity is observed in the activation of allenes. For the lactonization of alkynoic acids, a different selectivity is observed compared to a standard gold(I) complex, demonstrating that the high local concentration due to a confined space can induce other selectivity in catalysis.
Keywords: cyclization reactions; gold catalysis; local concentration; nanospheres; supramolecular catalysis